2015
DOI: 10.1002/anie.201411882
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Hydroalkenylation of Vinylarenes: Electronic Effects of Substrates and Chiral N‐Heterocyclic Carbene Ligands

Abstract: An asymmetric tail-to-tail cross-hydroalkenylation of vinylarenes with terminal olefins was achieved by catalysis with NiH complexes bearing chiral N-heterocyclic carbenes (NHCs). The reaction provides branched gem-disubstituted olefins with high enantioselectivity (up to 94 % ee) and chemoselectivity (cross/homo product ratio: up to 99:1). Electronic effects of the substituents on the vinylarenes and on the N-aryl groups of the NHC ligands, but not a π,π-stacking mechanism, assist the steric effect and influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 63 publications
0
30
2
Order By: Relevance
“…2). It is worth mentioning that despite much exploration of the use of chiral NHCs, there has been less reports with nickel-catalyzed reactions 3140 . N -(2-Biphenyl)- ( L*1 ) and N -(2-isopropylphenyl)- ( L*2 ) substituted NHCs 41 were ineffective to give 3aa .…”
Section: Resultsmentioning
confidence: 99%
“…2). It is worth mentioning that despite much exploration of the use of chiral NHCs, there has been less reports with nickel-catalyzed reactions 3140 . N -(2-Biphenyl)- ( L*1 ) and N -(2-isopropylphenyl)- ( L*2 ) substituted NHCs 41 were ineffective to give 3aa .…”
Section: Resultsmentioning
confidence: 99%
“…1 . In a related reaction, Ho et al reported 42 dimerization of vinylarenes and 1-alkenes catalysed by N -heterocyclic carbene complexes of Ni( ii )-salts to give uncommon tail-to-tail dimerization products ( 7 , eqn (2)). …”
Section: Introductionmentioning
confidence: 99%
“…Because the steric demands of N ‐mesityl‐ and N ‐benzyl‐substituted NHCs are different,27 the effects of the electronic properties of the NHC ligands on this catalytic process could be compared in the series of N , N′ ‐dimesityl complexes 1b , 1c , 1a , 1g and 1h : that is, in the order of decreasing donor strength of ligands (IMes 2Me > IMes Me > IMes ≈ IMes OPiv > IMes O ). Because all of them provide the same yields of polystyrene, these results suggest that factors other than the electronics of the NHCs define the overall efficiency of this catalytic system 28…”
Section: Resultsmentioning
confidence: 76%